Anterior resection of rectum – selected quality of life aspects - Jabłońska, Iwona; Czupryna, Antoni; Kulig, Jan; Legutko, Janusz (Contemporary Oncology/Współczesna Onkologia, 2006)
Colorectal cancer (CRC), is a serious and growing problem not only in Poland but also worldwide. Quality of life questionnaires are valuable sources of information which integrate laboratory and diagnostic data. The aim of the study was to assess the quality of life of patients who underwent anterior resection and chemotherapy, and to find out the most common physical and psychological complaints that affect quality of life also. A group of 35 persons were assessed, who experience strongly their own condition, and for whom psychological disorders have the same intensity as physical disorders. Most of the examined persons, 52%, evaluated their own quality of life as ”good” or ”very good”. An average patient evaluates their own quality of life as ”rather good” in the Rotterdam scale. However, they evaluate their own health as lower, indicating it as ”neither good nor bad”. Based on the study of the outcomes, the following conclusions were drawn: 1) the outcomes of questionnaires of quality of life of patients with colorectal cancer treated by anterior resection are various so far; 2) the knowledge of quality of life in this group is still too low; 3) the monitoring of quality of life of people with colon cancer after anterior amputation of rectum and chemotherapy has to be a basic part of therapy.